2021
DOI: 10.3389/fpubh.2021.664709
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Reach of an Evidence-Based, System-Level, Racial Equity Intervention: Translating ACCURE to the Maternal Healthcare and Education Systems

Abstract: The abundance of literature documenting the impact of racism on health disparities requires additional theoretical, statistical, and conceptual contributions to illustrate how anti-racist interventions can be an important strategy to reduce racial inequities and improve population health. Accountability for Cancer Care through Undoing Racism and Equity (ACCURE) was an NIH-funded intervention that utilized an antiracism lens and community-based participatory research (CBPR) approaches to address Black-White dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Put otherwise, redistributive or ‘liberatory’ interventions may be (un)intentionally delimited to the priorities of dominant interest groups and public health ‘professionals’ [ 119 ]. In praxes rooted in CRT, the perspectives of socially marginalized groups should constitute the main axis by which all discourse and decisions take place – the principle of “centering the margins” [ 120 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Put otherwise, redistributive or ‘liberatory’ interventions may be (un)intentionally delimited to the priorities of dominant interest groups and public health ‘professionals’ [ 119 ]. In praxes rooted in CRT, the perspectives of socially marginalized groups should constitute the main axis by which all discourse and decisions take place – the principle of “centering the margins” [ 120 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of ABR as a public health crisis alone cannot challenge harmful racial hierarchies, and the interventions showcased in this review are but a starting point for the gaps identified in culturally safe outcome evaluation and community leadership. Participatory engagement of stakeholders, through multiple intervention arms and sectors, who are mutually informed and committed to an ethic of transformation (and simultaneously, refusal to engage in or with, exclusionary systems), are important practices to bridge gaps [ 120 ]. Public health institutions should further mobilize action on enduring infrastructure and legislative change that would foster permanent distributive and procedural justice across contexts.…”
Section: Discussionmentioning
confidence: 99%
“…This prior formative work following the Undoing Racism principle of analyzing power led GHDC to focus on transparency as a key principle in its approach to racial equity interventions. With these foundations, ACCURE operationalized transparency and the Undoing Racism concept of maintaining accountability through intervention components at the community, organizational, and interpersonal levels, described in detail elsewhere (Baker et al, 2021, Cykert et al, 2020. For the present analysis, we focused on ACCURE's nurse navigation which was conceptualized as an accountability intervention compo-nent.…”
Section: Eliminating Cancer Care Disparities: the Accure Interventionmentioning
confidence: 99%